Analysis of Haptoglobin and Hemoglobin-Haptoglobin Interactions with the Neisseria meningitidis TonB-Dependent Receptor HpuAB by Flow Cytometry - Rohde, Kyle H. (American Society for Microbiology, 2004)
Neisseria meningitidis expresses a two-component TonB-dependent receptor, HpuAB, which mediates heme-iron (Hm-Fe) acquisition from hemoglobin and hemoglobin-haptoglobin complexes. Due to genetic polymorphisms in the human haptoglobin gene, haptoglobin (and hemoglobin-haptoglobin) exists as three structurally distinct phenotypes. In this study, we examined the influence of the haptoglobin phenotype on the interactions of HpuAB with apo-haptoglobin and hemoglobin-haptoglobin. Growth assays confirmed that HpuAB utilizes hemoglobin-haptoglobin more efficiently than hemoglobin as an Fe source and revealed a preference for human-specific, polymeric 2-2 or 2-1 hemoglobin-haptoglobin complexes. We developed a flow cytometry-based assay to measure the binding kinetics of fluorescein-labeled ligands to HpuAB on live, intact meningococci. The binding affinity of HpuAB for hemoglobin-haptoglobin phenotypes correlated well with the ability of each ligand to support Neisseria meningitidis growth, with higher affinities exhibited for types 2-2 and 2-1 hemoglobin-haptoglobin. Saturable binding of Hb and apo-haptoglobin suggested that HpuAB-mediated utilization of hemoglobin-haptoglobin involves specific interactions with both components. In contrast to previous studies, we detected binding of HpuB expressed alone to hemoglobin, apo-haptoglobin, and hemoglobon-haptoglobin of all three phenotypes. However, in the absence of HpuA, the binding capacity and/or affinity of the receptor was reduced and the dissociation of hemoglobin was impaired. We did not detect binding of HpuA alone to hemoglobin, apo-haptoglobin, or hemoglobin-haptoglobin; however, the lipoprotein is crucial for optimal recognition and use of ligands by the receptor. Finally, this study confirmed the integral role of TonB and the proton motive force in the binding and dissociation of Hb and hemoglobin-haptoglobin from HpuAB.